2022
DOI: 10.3390/foods11030313
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity of Extracellular Vesicles of Kimchi-Derived Lactic Acid Bacteria (Leuconostoc mesenteroides, Latilactobacillus curvatus, and Lactiplantibacillus plantarum)

Abstract: Lactic acid bacteria present in Kimchi, such as Leuconostoc mesenteroides (Lm), Latilactobacillus curvatus (Lc), and Lactiplantibacillus plantarum (Lp) produce extracellular vesicles (ECVs) that modulate immune responses. The ECVs of probiotic Kimchi bacteria are abbreviated as LmV, LcV, and LpV. Treatment of macrophages (RAW264.7) with ECVs (LmV, LcV, and LpV) increased the production of nitric oxide (NO), tumor necrosis factor (TNF)-α, and interleukin-6 (IL-6). Immunostimulatory effects exerted on the RAW264… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…EVs from Leuconostoc mesenteroides, Latilactobacillus curvatus , and Lactiplantibacillus plantarum significantly inhibited the production of NO and pro-inflammatory cytokine by LPS-stimulated microglia cells with neuroinflammation. This inhibitory effect is associated with the suppression of the MAPK signaling pathways through phosphorylation of p38 and ERK [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EVs from Leuconostoc mesenteroides, Latilactobacillus curvatus , and Lactiplantibacillus plantarum significantly inhibited the production of NO and pro-inflammatory cytokine by LPS-stimulated microglia cells with neuroinflammation. This inhibitory effect is associated with the suppression of the MAPK signaling pathways through phosphorylation of p38 and ERK [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…LAB also exerts immunostimulatory effects as demonstrated in macrophage cells and T-lymphocytes isolated from the spleen of mice [ 52 ]. Tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and nuclear factor-kappa B (NF-KB) are proteins that are directly involved in neuroinflammatory processes and the activation of microglia [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable iterative development of our purification method in a high throughput fashion, we utilized the mouse macrophage cell line RAW264.7. The RAW264.7 cell line has previously been validated to recapitulate in vivo anti‐inflammatory responses of EVs, and for study of in vitro anti‐inflammatory bioactivity of BEVs (Hu et al, 2020; Kim et al, 2022; Pacienza et al, 2019). In L. casei AEC elution fractions, we observed high particle counts (Figure 2d), presence of BEVs in electron micrographs (Figure 2e), and anti‐inflammatory bioactivity (Figure 2f), altogether indicating that AEC can separate L. casei BEVs.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that there is a mechanism by which molecules with immunomodulatory ability are secreted from microorganisms that have beneficial effects to the outside of the cell and delivered to the target cell of the living body [131]. When various EVs derived from bifizus, butyric-acid, and lactic-acid bacteria were added to two types of immune cells, mouse macrophage-like-cell line RAW264.7 and dendritic-cell line DC2.4, the production of inflammatory cytokines, tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6) was increased [132][133][134][135]. This report confirmed that EVs derived from probiotics have immunostimulatory abilities.…”
Section: Modification Of Evs As Dds Methodsmentioning
confidence: 99%